Cloud formation in metal-rich atmospheres of hot super-Earths like 55 Cnc e and CoRoT7b. Issue 1 (2nd August 2017) - Mahapatra, G.; Helling, Ch.; Miguel, Y.
Abstract: Clouds form in the atmospheres of planets where they can determine the observable spectra, the albedo and phase curves. Cloud properties are determined by the local thermodynamical and chemical conditions of an atmospheric gas. A retrieval of gas abundances requires a comprehension of the cloud formation mechanisms under varying chemical conditions. With the aim of studying cloud formation in metal-rich atmospheres, we explore the possibility of clouds in evaporating exoplanets like CoRoT-7b and 55 Cancri e (55 Cnc e) in comparison to a generic set of solar abundances and the metal-rich gas giant HD 149026b. We assess the impact of metal-rich, non-solar element abundances on the gas-phase chemistry, and apply our kinetic, non-equilibrium cloud formation model to study cloud structures and their details. We provide an overview of global cloud properties in terms of material compositions, maximum particle formation rates and average cloud particle sizes for various sets of rocky element abundances. Our results suggest that the conditions on 55 Cnc e and HD 149026b should allow the formation of mineral clouds in their atmosphere. The high temperatures on some hot rocky super-Earths (e.g. the day side of CoRoT-7b) result in an ionized atmospheric gas, and they prevent gas condensation, making cloud formation unlikely on its day side.